Resource and environment conservation in smallholder rice production using leaf color chart based nitrogen application - KUMARI, CHANDA; SINGH, GARIMA; GHOSH, MAINAK; KUMAR, SANJAY; KOHLI, ANSHUMAN (Journal of Soil and Water Conservation, 2022)
The inadequate nitrogen fertilizer consumption in Indian agriculture has adversely affected the sustainable crop production and poses threat to the environment. The global anthropogenic N2O emission from the synthetic N fertilizer application has escalated over the past few decades and can only be resolved by the use of precise amount of fertilizer for the crop avoiding its overuse. Optimization of plant nitrogen requirement using leaf colour chart (LCC) has direct impact on increasing N utilization by reducing the N dose without hampering the economic yield and the environment. The adequate N utilization can be achieved through the use of leaf colour chart (LCC) at different growth stages by feeding the N as per need of the crop. Experiment was carried out during 2019 in kharif season to analyze the performance of rice crop under different N rates applied using LCC on sandy clay loam soil of eastern India in randomized block design with seven treatments, replicated thrice. Among the seven treatments, the six were LCC based N management where three LCC thresholds (3.5, 4.0 and 4.5) were fixed in combination with two N levels (25 and 30 kg N ha-1) for top dressing whenever 60% of LCC reading was noted below the fixed threshold and one N omitted treatment was kept as control. Impact of differing N rates showed that the grain yield was achieved under LCC threshold <4.0 with 25 kg N ha- 1 in split (3978 kg ha-1) against the total N 105 kg ha-1 maintained the similar grain yield with the same LCC threshold having 30 kg N ha-1 in split and higher LCC threshold (<4.5) with 25 kg N ha-1 in split with the saving of 14.3 and 23.8% N application, respectively. Study confirmed that Leaf Color Chart based N management especially under the LCC <4.0 with 25 kg N ha-1 in split can save considerable amount of N along with maintain the short duration rice production.